Answers

2015-06-22T21:09:05+08:00
For example, (x+y)³= x³+3x²y+3xy²+y³
First term: (x)³= x³
Second term:3(x)²(y)= 3x²y
Third term:3(x)(y)²= 3xy²
Last term:(y)³= y³



0
2015-06-22T21:16:53+08:00
CUBE OF A BINOMIAL
It is the cube of two terms separated by a sign (subtraction or addition).

FORMULA:
First Term: The cube of 1st term
Second Term: 3 times the product of 1st term (squared) and 2nd term
Third Term: 3 times the product of 1st term and 2nd term (squared)
Fourth Term: The cube of 2nd term
0